Market integration with ASEAN and beyond: The case of Myanmar - Ajmani, Manmeet Singh; Joshi, Pramod Kumar; Vr, Renjini; Roy, Devesh (International Food Policy Research Institute, 2018)
In this paper, we address the question of market integration of Myanmar with the Association of Southeast Asian Nations (ASEAN) and its other top trading partners. Focusing on agricultural trade, we use indicators – ‘Trade Potential’ and ‘Competition Indices’ to assess the nature and extent of the integration. This study highlights the exports of Myanmar which are competitive in the ASEAN markets and have high export potential. A higher trade potential with lower competition (value or volume) would indicate an opportunity for higher returns for agricultural producers. In the case of Myanmar, “dried legumes and beans,” “crustaceans,” “frozen fish,” “other oilseeds,” “maize,” and “preserved fruits and nuts” are identified as high-potential exports with lower competition in ASEAN markets which can be targeted for trade expansion. Finally, to demonstrate the upward movement in the value chain, possibly due to quality upgradation, we present the dynamics of the unit value of Myanmar’s agricultural exports.